Compact gain switched optical frequency comb generator for sensing applications. (July 2019) - Hammad, M N; Martin, E P; Deseada Gutierrez, M; Lakshmijayasimha, P D; Jain, G; Landais, P; Braddell, J; Anandarajah, P M
Abstract: We present a novel InP photonically integrated optically injected device that is gain switched for the generation of an optical frequency comb. Using this technique, an optical frequency comb with a free spectral range of 6.25 GHz and nine spectral lines within a 3 dB spectral window is obtained. Such a device provides tunability of both the free spectral range and the centre emission wavelength, which facilitates the matching of the wavelength to the signature of a target gas. The stable spacing and high phase correlation between the comb lines confirms the potential of the device to be used in various applications such as spectroscopy, telecommunications and gas sensing.